Displaced in Place: Manufactured Housing, Mass Eviction, and the Paradox of State Intervention. (April 2017) - Sullivan, Esther
This article examines housing insecurity within manufactured housing—the single largest source of unsubsidized affordable housing in the United States, home to about 18 million low-income residents. A large portion of manufactured housing is installed in mobile home parks, which can legally close at any time, displacing entire communities. Based on two years living within and being evicted from closing mobile home parks in two states, this comparative ethnography of mass eviction juxtaposes sites of distinctive state practices for managing the forced relocation of park residents. I analyze the experience of eviction in Florida, a site of explicit intervention and "model" legislation for mobile home park closures, in light of the experience in Texas, where the state has adopted a hands-off approach. I describe the paradoxical effects of Florida's protective, yet market-oriented, state housing interventions, which produced both a cottage industry of mobile home relocation services and a more protracted, pernicious eviction for displaced residents. I outline the specific mechanisms through which this paradox of state intervention occurred and consider the implications not only for mobile home parks but also for a variety of other state programs that are currently being delivered through an adaptive reliance on the private sector.